2014
DOI: 10.1002/ppul.23065
|View full text |Cite
|
Sign up to set email alerts
|

Val66Met polymorphism in the BDNF gene in children with bronchial asthma

Abstract: Specific BDNF gene polymorphism may contribute to bronchial asthma susceptibility. Our study suggested the positive association between selected functional BDNF polymorphism (rs6265) and asthma in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Furthermore, our results showed that the G allele of rs6265 is overrepresented in CA subjects, compared to the healthy controls. Similarly, a recent study demonstrated an association between this polymorphism and CA in a Slovakian population, and established the G allele as a risk factor for CA (Jesenak et al, 2014). This study confirmed the association of this putative functional polymorphism with CA in a Chinese Han population.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, our results showed that the G allele of rs6265 is overrepresented in CA subjects, compared to the healthy controls. Similarly, a recent study demonstrated an association between this polymorphism and CA in a Slovakian population, and established the G allele as a risk factor for CA (Jesenak et al, 2014). This study confirmed the association of this putative functional polymorphism with CA in a Chinese Han population.…”
Section: Discussionsupporting
confidence: 74%
“…Increased levels of BDNF in blood, broncho-alveolar lavage fluid, and nasal lavage fluid have been positively correlated with increased disease activity and severity in patients with asthma (Muller et al, 2010). Our results provide direct evidence of a link between a genetic change in BDNF and CA incidence, and proposed the variants that may affect the development of CA (Jesenak et al, 2014).…”
Section: Discussionsupporting
confidence: 50%
“…The regulated secretion of neurotrophins in these cells is under the control of intracellular Ca 2+ 53,55 and cAMP 56. Moreover, the Val66Met polymorphism in the BDNF gene has been linked to pathological conditions in the airways such as asthma;57,58 whether this polymorphism affects the secretion of BDNF as in neuronal cells needs further investigation.…”
Section: Secretion Of Neurotrophins From Non-neuronal Tissuesmentioning
confidence: 99%
“…The association of rs6265‐T with ileal disease location might therefore be due to earlier smoking in our rs6265‐T patients, triggering and shaping an immunological response at a vulnerable age. Interestingly, rs6265‐T enhanced protective effects of smoking in melanoma and increased the risk of childhood asthma . Several lines of evidence also indicate a direct role of brain‐derived neurotrophic factor (BDNF) on the immune and nervous system of the gut .…”
Section: Discussionmentioning
confidence: 99%